Impact of surgical approach and size of femoral head in risk of dislocation post total hip arthroplasty - Belbase, Rupesh Jung; Limbu, Kumud; Basnet, Anil Kumar; Regmi, Pushpak (International Journal of Research in Orthopaedics, 2023)
Background: Total hip arthroplasty (THA) is one of the orthopedic procedures that are both economical and routinely successful. THA offers dependable benefits for patients with end-stage degenerative hip osteoarthritis (OA), including pain alleviation, functional recovery, and overall better quality of life. Methods: This was a retrospective study which was conducted on patients who visited the hospital’s outpatient department received THA and also received the revisions of THA, were included. The reasons for THA were analyzed and their revisions were studied. The patients were studied according to various approaches based on the hip surgery, such as, straight lateral, anterolateral, posterolateral, and anterior and also based on the sizes divided into three groups 22-28 mm, 32 mm, and 36 mm. Results: The posterolateral approach (n=40) was used for the majority of THAs, followed by the straight lateral (n=35), anterior (n=25), and anterolateral (n=20) approaches. 22.5% of THAs that were done with a posterolateral approach used a 36-mm head. Each reason for different size of heads have been statistically analyzed. During the six-year follow-up, this (unadjusted) risk was 1.15% for femoral heads measuring 22 to 28 mm. THA with 32-mm heads had a considerably decreased risk of revision for dislocation (0.75%), compared to 36-mm heads (0.55%). Conclusions: The study concluded that the patients who received THA at posterolateral approach, experienced dislocations more frequently and also it has been found that the patients using 22 to 28 mm femoral head had more dislocations.